MANAJEMEN RANTAI PASOK (SUPPLY CHAIN) BENIH PADI PADA CV. PRIANGAN TIMUR SEED COMMUNITY (PTSC) - Novia, Fajria; Nuraini, Candra; Mutolib, Abdul (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Every company requires efficient chain performance in meeting consumer demand so that it can compete and optimize profits. The objectives of this study are (1) Identifying the rice supply chain mechanism at CV. PTSC, and (2) Analyzing the performance of the rice seed supply chain at CV. PTSC.  The research method used is descriptive qualitative and quantitative methods. The research was conducted in July - December 2023 located at CV. PTSC Banjarsari. Measurement of supply chain management performance using the supply chain operation reference (SCOR) analysis method. The results of the analysis of the comparison of the average value of supply chain performance measurements on farmers show that the Responsiveness, Flexibility, and Asset Performance Attributes are already in a Superior position, but the Reliability performance attribute on delivery performance, which is an average of 88.24 percent and standard conformity of 88.14 percent, the value of supply chain performance is still in the Parity position, which means that it has not yet reached a good enough condition. Comparison of the average value of supply chain performance measurements at CV. PTSC shows that the Reliability, Responsiveness and Flexibility Performance Attributes are already in a Superior position. Keyword: Rice Seeds, Supply Chain Management, CV. PTSC Abstrak: Setiap perusahaan memerlukan kinerja rantai yang efisien dalam memenuhi permintaan konsumen sehingga mampu bersaing dan dapat mengoptimalkan keuntungan. Tujuan dari penelitian ini yaitu (1) Mengidentifikasi mekanisme rantai pasok padi pada CV. PTSC, dan (2) Menganalisis kinerja rantai pasok benih padi pada CV. PTSC.  Metode penelitian yang digunakan adalah metode deskriptif kualitatif dan kuantitatif. Penelitian dilaksanakan pada Bulan Juli – Desember 2023 yang berlokasi di CV. PTSC Banjarsari. Pengukuran kinerja manajemen rantai pasok menggunakan metode analisis supply chain operation reference  (SCOR). Hasil analisis perbandingan nilai rata-rata pengukuran kinerja rantai pasok  pada petani menunjukkan Atribut Kinerja Responsivenes, Flexibility, dan Asset sudah berada di posisi Superior, namun atribut kinerja Reliability pada kinerja pengiriman yaitu rata-rata sebesar 88,24 persen dan kesesuaian standar sebesar 88,14 persen nilai kinerja rantai pasok tersebut masih berada di posisi Parity, yang artinya belum mencapai kondisi yang cukup baik. Perbandingan nilai rata-rata pengukuran kinerja rantai pasok  pada CV. PTSC menunjukkan Atribut Kinerja Reliability, Responsivenes dan Flexibility sudah berada di posisi Superior. Kata kunci: Benih Padi, Manajemen Rantai Pasok, CV. PTSC.